Determinants of Technology Acceptance Model (TAM) towards ICT Use for English Language Learning - Urip Sulistiyo; Tubagus Zam Zam Al Arif; Reli Handayani; M. Faruq Ubaidillah; Mujiyono Wiryotinoyo (National Research University Higher School of Economics, 2022)
Background: The use of ICT in learning English can assist learners to improve their language skills, aside from empowering and motivating them in English language learning. ICT utilization can provide opportunities for collaboration and interaction in the learning process. Purpose: The present study was conducted to examine the motivation, ICT skills, equipment, and attitudes factors towards the use of ICT tools for English learning in English as a Foreign Language (EFL) context. Method: The quantitative method was applied involving 303 pre-service teachers of English department at a state university in Jambi, Indonesia. A questionnaire was employed to collect the data and Structural Equation Modeling (SEM) was used to analyze the proposed hypotheses developed in fulfilling the study objectives. Technology Acceptance Model (TAM) was used to examine the attitudes of student teachers toward the use of ICT for English language learning. Results: Findings suggested that the determinants of the technology acceptance model are the major factors influencing the usage of ICT. In addition, the effect of equipment, motivation, and ICT skills towards the use of ICT had been mediated by three main variables of TAM, namely perceived ease of use, perceived usefulness, and attitudes. Furthermore, it was found that the motivation, ICT skills and attitudes factors affect the actual use of ICT for English learning while the equipment factor does not. Implication: The results of this study are beneficial for students and teachers both in schools and universities. For students, they need to equip themselves with ICT literacy, ICT skills, motivation, and positive attitudes towards the use of ICT in English learning activities. Teachers should also equip themselves with ICT skills so that they can provide learning experiences according to the needs of students in today's digital age.